Kajian Dampak Ekonomi Hutan Desa Terhadap Pendapatan Petani Kampung Merabu (Kabupaten Berau, Provinsi Kalimantan Timur) - Roy, Juliansyah; Kuncoro, Mudrajad; Darma, Dio Caisar (IQTISHODUNA, 2019)
The purpose of this study is to answer the prior problems of analyzing the extent to which the effect of the duration of the decision letter is accepted, the size of the land, the number of labor, the transportation costs, the input costs, the partnership pattern, the knowledge of the status of the village forest, the participation of planning and implementation participation, and the participation of monev on farmer income in Merabu. The research method used in this research is explorative and analytical descriptive. In general, there is an increase in production, income and employment. Regression analysis proves that the length of the decision letter is accepted and the amount of labour has a positive effect on income significantly. Meanwhile, labour is a dominant variable affecting the income of Merabu. Since the status of village forests is published in 2014, farmers are beginning to transform to manage and utilize forest land. The number of workers had increased quite drastically from before and after the village forest decree received.